Analisis Perbedaan Tingkat Pengungkapan Corporate Social Responsibility (CSR) dan Kinerja Keuangan Perusahaan pada Industri High-Profile dan Low-Profile - Sisilia Devina Permatasari; Supatmi Supatmi (Forum Manajemen Indonesia (FMI), 2016)
This study aims to prove the difference in the level of disclosure of Corporate Social Responsibility (CSR) and financial performance among the industry's high-profile and low-profile. This study also proved that if there is a relationship between the level of CSR and financial performance. Financial performance is measured using the Return On Equity (ROE) and Tobin's Q. The samples are 346 companies listed in Indonesia Stock Exchange (IDX) in 2012, where the industry as much as 167 high-profile and low-profile companies as much as 179 companies. The sampling method used is purposive sampling. The analyze used to test Mann-Whitney test first, while the second test using Spearman correlation test. The results of this study indicate that there are differences in the level of disclosure of CSR and financial performance as measured by Tobin's Q between industrial high-profile and low-profile, but did not differ when performance is measured by ROE. In addition, this study proves that there is a positive relationship between the level of CSR and financial performance as measured by ROE, but there is no relationship between the level of CSR and financial performance as measured by Tobin's Q. Keywords : Corporate Social Responsibility Disclosure, ROE, Tobin’s Q, high-profile and low-profile industries.